فهم السياق القرآني لدى المفسرين بين التوجيه اللغوي والتذوق البلاغي: UNDERSTANDING THE QUR'ANIC CONTEXT FOR THE INTERPRETERS BETWEEN LINGUISTIC GUIDANCE AND RHETORICAL TASTE - Abdul Ghani Bin Md Din; Omar bin Md Din; Ummu Hani Abas; Ragab Ibrahim Ahmed Awad; Mohd Azizul Rahman Bin Zabidin (Maʿālim al-Qurʾān wa al-Sunnah, 2022)
This research aims to demonstrate the efforts of linguistic and rhetorical interpreters in the quest of al Qur’an meanings’ clarification and extract Islamic sharia provisions with reference to Arabic language arts such as grammar, morphology, rhetoric and dictionaries, as well as the sciences of jurisprudence, logic and others. That is by choosing, studying and clarifying some of the words of the Qur’an such as the difference between “creates and does,” and “from its places,” “after its places,” the different meanings in “laughed,” and proportionality in the context of “hunger and thirst,” and clarifying the significance of the consequence and becoming. The research attempts to answer several questions, the most important of which are: What is the role of the Arabic grammar, dictionaries, morphology and rhetoric in clarifying the purposes of vocabulary and Quranic texts and how did the interpreters manage to adapt Arabic language arts in order to understand the Qur’anic text as well as to extract Islamic sharia provisions. The research used the descriptive analytical method to demonstrate how interpreters use Arabic language arts in order to understand the Qur’anic text. The research reached several results, including that the interpreters pay attention to the linguistic levels during their analysis of the Qur’anic verses, starting from the meanings of the vocabulary to the relationships of the sentences and the context of the text; they use the verses to demonstrate al Qur’an miracles and to derive the Islamic sharia provisions.